Going Mobile : the Personalized, On-Demand Future of Urban Transportation - Sumantran, Venkat; Fine, Charles; Gonsalvez, David (MIT Sloan Management Review, 2018)
Throughout the 20th century, autos and the auto industry propelled human development, bringing unrivalled utility and flexibility to the way people move. Yet the industry now faces fundamental disruption as vehicle ownership yields to on-demand mobility.